GaN nanocolumn arrays with diameter <30 nm prepared by two‐step selective area growth. Issue 25 (1st December 2015) - Kano, T.; Yoshida, J.; Miyagawa, R.; Mizuno, Y.; Oto, T.; Kishino, K.
Abstract : A new method of two‐step selective area growth (SAG) by RF‐plasma‐assisted molecular beam epitaxy is developed, enabling the growth of uniform arrays of thin GaN nanocolumns (NCs) with diameters <50 nm. In the SAG, the migration‐enhanced epitaxy mode with an alternating supply of Ga and active nitrogen was employed during the initial growth of NCs on small‐nanohole‐patterned substrates to complete the crystal nucleation in the nanoholes. Once the nucleation occurred, the growth mode to the simultaneous supply of Ga and nitrogen is immediately switched. In the second step, the growth temperature is increased and the nitrogen flow rate to suppress the lateral growth rate is decreased. A high‐density uniform array of very thin NCs in a triangular lattice with a diameter of 26 nm and a lattice constant of 60 nm is demonstrated; the NC density is 3.2 × 10 10 cm −2 .